1996
DOI: 10.1007/bf02745154
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of cobalt doped cadmium oxalate crystals

Abstract: CoxCdl_xC2044H20 crystals grown by gel technique are characterized for dielectric properties by optical absorption measurements. Loss curve shows a relaxation peak at 500 KHz corresponding to a relaxation time of 0"3 #s. Cole-Cole diagrams give exponent of universal power law to be equal to 0'22. Optical absorption shows peaks due to Co ÷ 2 ion and water of hydration. An attempt is made to understand the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 7 publications
(6 reference statements)
0
20
0
Order By: Relevance
“…From these Arrhenius graphs, the values of activation energy E and pre-exponential factor A thus calculated are shown in Table 1. It was observed that the values of activation energy E, for etching in HCl, NH 4 Cl and HNO 3 solutions are close to each other, though the rates of dissolution in these etchants are largely different. BaCl 2 and NH 4 Cl + HCl etch solutions are characterized by relatively larger and lower values of activation energies respectively.…”
Section: Observations Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…From these Arrhenius graphs, the values of activation energy E and pre-exponential factor A thus calculated are shown in Table 1. It was observed that the values of activation energy E, for etching in HCl, NH 4 Cl and HNO 3 solutions are close to each other, though the rates of dissolution in these etchants are largely different. BaCl 2 and NH 4 Cl + HCl etch solutions are characterized by relatively larger and lower values of activation energies respectively.…”
Section: Observations Results and Discussionmentioning
confidence: 92%
“…BaCl 2 and NH 4 Cl + HCl etch solutions are characterized by relatively larger and lower values of activation energies respectively. The faster etch rate in NH 4 Cl-HCl may not be due to the energies of the atoms at the surface or due to their geometric configuration [23], but may be due to both; the chemical reaction and diffusion are operating simultaneously, that makes the etching or dissolution process less sensitive to temperature change, and hence a very low value of activation energy was observed. The etchants such as HCl, HNO 3 reacts with the crystal surface to form oxalic acid, which in turn dissolves in water.…”
Section: Observations Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the figs, it is found that the values of dielectric constant and dielectric loss decreases with the increase in frequency and dielectric constant of crystal at higher frequencies is almost constant. The very high value of ɛ r at low frequencies may be due to the presence of all the four polarizations, namely space charge, orientional, ionic and electronic polarizations and its low value at high frequencies may be due to the loss of significance of these polarizations gradually [17]. The value of dielectric loss at high frequencies reveals the high optical quality of the crystal with lesser defects, which is the desirable property for NLO applications [18].…”
Section: Dielectric Propertiesmentioning
confidence: 99%